The Queen of Herb with Potent Therapeutic Constituent in Various Disease States: A Reappraisal - Md Harun Al Rashid,; Anindya Banerjee,; Nigam Jyoti Maiti, (International Journal of Phytomedicine, 2013)
Ocimum sanctum Linn has been used extensively for its medicinal value in India and China. In traditional system of medicine, different parts (leave, stem, flower, root, seed and even whole plant) of O. sanctum L. (Tulsi in Hindi and Vasub in Arabic), a small herb seen throughout in India. O. sanctum have been recommended for the treatment of bronchitis, bronchial asthma, malaria, diarrhea, dysentery, skin disease, arthritis, painful eye disease, chronic fever, insect bite etc. It has also been suggested to possess antifertility, anticancer, antidiabetic, antifungal, antimicrobial, hepatoprotective, cardio-protective, antiemetic, antispasmodic, adoptogenic and diaphoretic activity. Current scientific research revealed that O. sanctum exhibit significant anticancer activity by enhancing antioxidant potential of gastric mucosa thereby reducing mucosal damage and reduces stress; enhances stermina and endurance ;boosts the immune system, reduces inflammation; lessens aging factors; supports the heart, lungs and liver.